Extensive Deep Venous Thrombosis Resulting from Anterior Lumbar Spine Surgery in a Patient with Iliac Vein Compression Syndrome: A Case Report and Literature Review. (August 2015) - Reddy, Deepak; Mikhael, Mark M.; Shapiro, Gary S.; Farrell, Tony
Study Design: Case report. Objective: Although May-Thurner syndrome or iliac vein compression syndrome is covered in the vascular literature, it remains absent from the orthopedic and neurosurgery literature and has not been previously reported to occur in concordance with spine surgery. We review the salient points of disease presentation, diagnosis, and treatment. Methods: A 33-year-old woman was followed postoperatively via clinical and radiographic findings. Her presentation, operative treatment, postoperative extensive deep venous thrombosis (DVT) formation, and management are described. Results: We present a unique case of a healthy 33-year-old woman who developed an extensive left iliac vein DVT after anterior lumbar spine fusion. Although she had multiple risk factors for thrombosis, the size of the thrombus was atypical. A subsequent venogram showed compression of the left common iliac vein by the right common iliac artery, consistent with May-Thurner syndrome. Conclusions: May-Thurner syndrome or iliac vein compression syndrome is a rare diagnosis that is absent from the spine literature. The condition can predispose patients to extensive iliac vein DVT. The contributing anatomy and subsequent clot often require catheter-directed thrombolysis and stenting to achieve a favorable outcome.